Islamic Banks in the Global Economy with Special Reference to in CIS Countries - Antropov, Vladislav V.; Strelkova, Irina Ð. (Journal of Reviews on Global Economics, 2020)
The subject of the article is Islamic banks – a special form of banking business, in which services are provided to customers on an interest-free basis. The article discusses the reasons why Islamic banks emerged and spread, and considers the dynamics and geographical distribution of their assets in the world economy. Particular attention is paid to the theory and practice of Islamic banks performance, their main differences from conventional banks, as well as basic mechanisms of Islamic financing. Problems that make it difficult for Islamic banks to expand in non-Muslim countries have been revealed. The experience of Islamic banks in the post-Soviet space has been analyzed, and the practical experience and success of these financial institutions have been considered.